Ω-6 Polyunsaturated Fatty Acids and Cardiometabolic Health: Current Evidence, Controversies, and Research Gaps. Issue 6 (4th September 2018) - Maki, Kevin C; Eren, Fulya; Cassens, Martha E; Dicklin, Mary R; Davidson, Michael H
ABSTRACT: The 2015 Dietary Guidelines for Americans recommend limiting the intake of saturated fatty acids (SFAs) to <10% of energy/d and replacing dietary SFAs with unsaturated fatty acids. A Presidential Advisory from the American Heart Association recently released its evaluation of the relation between dietary fats and cardiovascular disease (CVD), and also recommended a shift from SFAs to unsaturated fatty acids, especially polyunsaturated fatty acids (PUFAs), in conjunction with a healthy dietary pattern. However, the suggestion to increase the intake of PUFAs in general, and omega-6 (n–6) PUFAs in particular, continues to be controversial. This review was undertaken to provide an overview of the evidence and controversies regarding the effects of ω-6 PUFAs on cardiometabolic health, with emphasis on risks and risk factors for CVD (coronary heart disease and stroke) and type 2 diabetes mellitus (T2D). Results from observational studies show that higher intake of ω-6 PUFAs, when compared with SFAs or carbohydrate, is associated with lower risks for CVD events (10–30%), CVD and total mortality (10–40%), and T2D (20–50%). Findings from intervention studies on cardiometabolic risk factors suggest that ω-6 PUFAs reduce concentrations of LDL cholesterol and non-HDL cholesterol in a dose-dependent manner compared with dietary carbohydrate, and have a neutral effect on blood pressure. Despite the concern that ω-6 fatty acids increase inflammation, current evidence from studies in humans does not support this view. In conclusion, these findings support current recommendations to emphasize consumption of ω-6 PUFAs as a replacement of SFAs; additional randomized controlled trials with cardiometabolic disease outcomes will help to more clearly define the benefits and risks of this policy.